Ove Jørgensen & Tore Nyberg: Sejlruter i Adam af Bremens øverden (Kungl. Vitterhets Historie og Antikvitets Akademien, Antikvarisk Arkiv 74, Almquist & Wiksell Int., 1992). 37 s., 70,-SEK. - Bøgh, Anders (Historie/Jyske Samlinger, 1994)
-